Biotechnological methods for improving reproduction on sheep breeding program using laparoscopic artificial inseminations in Debrecen, Hungary - Zegeye, Zemenu Birhan; Magyar, Károly; Novotni-Dankó, Gabriella (Acta Agraria Debreceniensis, 2024)
The aim of this study was to evaluate the results of the LAI method in different types of breeds and seasonal variations. Analysing n=536 LAI in 7 years, there were no significant differences observed in the breed in lambing rates. Although the lambing rate of Prolific Merino (F+) was better than any other breed (45.3%). We found significant differences between breeds of Tzigaia, its pregnancy rate was 19.2%. In the case of prolificacy there were significant differences between breeds: Prolific Merino’s (FF) was the highest (2.38) and, Indigenous Tzigaia’s was the lowest (1.4) from all of them. The obtained results showed that summer inseminations were the most effective in concern of pregnancy rate (49.5%). The results are based on use of the types of semen, showed that using frozen semen was most effective than fresh semen in both parameters, however there were no significant differences. Summarising all tested conditions in our study breeds, seasons and type of semen using LAI the total results of pregnancy rate was 40.3% and the prolificacy was 1.78, respectively. Follow up the out-of-season ovarian, progesterone level of n=36 Prolific Merino were examined and insulin, IGF-1, leptin, T3, and T4 hormones as well, to evaluate the energetic status of the flock. Progesterone analysis showed 43% of examined ewes had a cyclical ovarian function in April and a cyclical ones had good reaction for estrus-induction hormonal treatment. Our results showed that valuable information can be obtained about energy supply from the determination of some metabolic hormones as IGF-1, insulin, leptin.